Implementation of the Policy on Screening, Identification, Assessment, and Support by Teachers in Selected Primary Schools in King Cetshwayo District - Msane, Hlakaniphile; Hlongwane, Mandla; Kent, Chedza (American Journal of Education and Practice, 2023)
Purpose: The study aimed to explore the implementation of the Screening, Identification, Assessment, and Support policy. It underpinned by the Bio-Ecological systems Theory (BEST) which outlines the importance of the surroundings and the interaction of the surrounding in the social and cognitive development of a child. Methodology: Data was gathered from a sample 32 participants comprising of 30 teachers from three primary schools and two district officials of the King Cetshwayo District. Survey questionnaires and focus groups interviews were used as data collection instruments. The data is presented into themes namely knowledge and understanding of the SIAS policy; addressing learning barriers identified in primary schools; teachers' knowledge and skills in working with learners with problems; common learning problems identified in primary schools; and impact of the SIAS policy to the development of learners. These main themes bred the sub-themes namely SIAS policy as a guideline; documented procedure on identifying learners with problems; supporting learners with learning problems as per the SIAS policy; parental involvement; teacher development about the notion of SIAS; cascaded training for teachers; behavioural problems; reading and writing problems; personal and scholastic development of learners; and general successes of the SIAS policy in the education setting. Findings: The key findings of the study revealed that SIAS policy of inclusive education is not effectively implemented. This is due to teachers not prepared enough in terms of skills and confidence in working with learners with learning problems. Recommendations: The research therefore recommends that training development needs to be well effected for teachers to align themselves with SIAS policy in working with learners with learning barriers.